Thermochemistry of hydroxymethylphenol isomers - da Silva, MAVR (2010)
The standard (p(o) = 0.1 MPa) molar enthalpies of formation in the crystalline state of the 2-,3- and 4-hydroxymethylphenols, Delta(f)H(m)(o)(cr) = -(377.7 +/- 1.4) kJ mol(-1), Delta(f)H(m)(o)(cr) = -(383.0 +/- 1.4) kJ mol(-1) and Delta(f)H(m)(o)(cr) = -(382.7 +/- 1.4) kJ mol(-1), respectively, were derived from the standardmolar energies of combustion, in oxygen, to yield CO(2)(g) and H(2)O(l), at T = 298.15 K, measured by static bomb combustion calorimetry. The Knudsen mass-loss effusion technique was used to measure the dependence of the vapour pressure of the solid isomers of hydroxymethylphenol with the temperature, from which the standard molar enthalpies of sublimation were derived using the Clausius-Clapeyron equation. The results were as follows: Delta(g)(cr)H(m)(o) = (99.5 +/- 1.5) kJ mol(-1), Delta(g)(cr)H(m)(o) = (116.0 +/- 3.7) kJ mol(-1) and D(cr)(g)H(m)(o) = (129.3 +/- 4.7) kJ mol(-1), for 2-, 3- and 4-hydroxymethylphenol, respectively. From these values, the standard molar enthalpies of formation of the title compounds in their gaseous phases, at T = 298.15 K, were derived and interpreted in terms of molecular structure. Moreover, using estimated values for the heat capacity differences between the gas and the crystal phases, the standard (p(o) = 0.1 MPa) molar enthalpies, entropies and Gibbs energies of sublimation, at T = 298.15 K, were derived for the three hydroxymethylphenols.